Social practices and University extension. Deconstruction of the imaginary of arts education based on extension experiences (Cuadernos de Extensión Universitaria de la UNLPam, 2021)
In this article, the importance of university networks is realized from a dialogue and comparative reflection between two extension references of Provincial Universities, the Provincial of Córdoba (UPC) and the Patagonian University Institute of the Arts (IUPA), with special attention to the artistic disciplines that are developed in both institutions, and focus on the territorial anchoring that gives meaning to the situated experience.From the experience in university extension, a proposal of analysis categories is developed towards a deconstruction of the imaginary of arts education in relation to the territories of the educational fact, the profile of the arts students, the emotional experience generated due to the artistic fact and the importance of the dialogue of knowledge in the joint design of an extension project and its sustainability. This dialogue is also part of an inter-institutional exploratory investigation of extension developments in arts majors from an integral point of view. It aims at curricular initiatives from the university careers chairs, but also to specific projects with other organizations and institutions, in coordination with state and civil society organizations, supported by dialogue between academic and community territories.
Keywords: art; extension; education; territory; of construction